Corannulene‐Fused Anion‐Responsive π‐Conjugated Molecules that Form Self‐Assemblies with Unique Electronic Properties. Issue 9 (28th June 2013) - Bando, Yuya; Sakurai, Tsuneaki; Seki, Shu; Maeda, Hiromitsu
Abstract The fusion of bowl‐shaped π‐conjugated corannulene units to anion‐responsive π‐conjugated dipyrrolyldiketone‐boron complexes resulted in new molecular materials with a unique self‐assembly capability. The bowl‐fused receptor with aliphatic tails could form both supramolecular gels and mesophases through π‐stacking interactions and also exhibited anion‐responsive characteristics. The presence of the π‐bowl unit not only afforded enhanced self‐assembly capability both in solution and in the mesophases, as evidenced by gelation experiments and phase‐transition profiles, but also enhanced intrinsic charge‐carrier mobility.